(untitled) (International journal of artificial intelligence, 2025)
This article delves into the linguocultural features of gastronomic metaphors in the English and Karakalpak languages, focusing on their usage in artistic texts from the 21st century. Gastronomic metaphors, as expressions of culinary terms that transcend their literal meanings, provide insight into cultural values, worldviews, and societal norms. The study examines how gastronomic metaphors are employed in both languages and explores their linguistic and cultural significance. Through the analysis of various literary texts, the paper highlights the similarities and differences in metaphorical usage and their role in shaping cultural identity. The research contributes to the understanding of the intersection between language, culture, and the world of gastronomy.